Pharmacodynamics and cellular accumulation of amphotericin B and miltefosine in Leishmania donovani-infected primary macrophages. (28th February 2018) - Voak, Andrew A; Standing, Joseph F; Sepúlveda, Nuno; Harris, Andy; Croft, Simon L; Seifert, Karin
Abstract: Objectives: We examined the in vitro pharmacodynamics and cellular accumulation of the standard anti-leishmanial drugs amphotericin B and miltefosine in intracellular Leishmania donovani amastigote–macrophage drug assays. Methods: Primary mouse macrophages were infected with L. donovani amastigotes. In time–kill assays infected macrophages were exposed to at least six different concentrations of serially diluted drugs and the percentage of infected macrophages was determined after 6, 12, 24, 48, 72 and 120 h of exposure. Cellular drug accumulation was measured following exposure to highly effective drug concentrations for 1, 6, 24, 48 and 72 h. Data were analysed through a mathematical model, relating drug concentration to the percentage of infected cells over time. Host cell membrane damage was evaluated through measurement of lactate dehydrogenase release. The effect of varying the serum and albumin concentrations in medium on the cellular accumulation levels of miltefosine was measured. Results: Amphotericin B was more potent than miltefosine (EC50 values of 0.65 and 1.26 μM, respectively) and displayed a wider therapeutic window in vitro . The kinetics of the cellular accumulation of amphotericin B was concentration- and formulation-dependent. At an extracellular concentration of 10 μM miltefosine maximum cellular drug levels preceded maximum anti-leishmanial kill. Miltefosine induced membrane damage in a concentration-, time- and serum-dependent manner. Its cellular accumulation levels increased with decreasing amounts of protein in assay medium. Conclusions: We have developed a novel approach to investigate the cellular pharmacology of anti-leishmanial drugs that serves as a model for the characterization of new drug candidates.